CLINICAL AND GENETIC PECULIARITIES OF ATRIAL FIBRILLATION - S. Y. Nikulina; V. A. Schulman; O. O. Kuznetsova; N. V. Aksjutina; P. A. Shesternja; A. A. Chernova; V. N. Maksimov; I. V. Kulikov; S. N. Ustinov; Y. L. Kazarinova; A. G. Romashchenko; M. I. Voevoda (Рациональная фармакотерапия в кардиологии)
Aim. To study inheritance patterns of atrial fibrillation (AF) and association of primary and secondary AF with gene polymorphism of β1-adrenoreceptors.Material and methods. 103 probands with AF and their 301 relatives of I, II, III degrees (basic group) and 82 probands without heart diseases and their 163 relatives of I and II degrees (control group) were examined. Examination included evaluation of electrophysiological indicators of sinoatrial node, electrocardiogram monitoring, veloergometry, echocardiography as well as assessment of gene polymorphism of β1-adrenoretseptors.Results. Accumulation of AF in probands families was founded. Segregation analysis of idiopathic AF revealed autosomal-dominant type of its inheritance.Сonclusion. The heterozygote genotype of gene β1-adrenoretseptors Ser49Gly is one of genetic predictors of primary and secondary AF.